Time-motion analysis of men's professional beach volleyball - Hammond, K. G.; Harry, Catherine Williams Hays, Brian K Schilling (Journal of Sport and Human Performance, 2020)
As the popularity of beach volleyball continues to grow, the evolution of sport-specific training has changed the level of competition at the elite level. In addition to sport-specific skills, training of the most utilized energy systems during competition can increase a team's chances of winning. The current study used time-motion analysis to analyze three men's professional beach volleyball finals matches to determine the typical number, type, and frequency of high-intensity movements by player position (blocker/defender) and outcome (win/loss). A Fisher's exact test determined if HIM frequency by positions and outcomes was statistically significant. Statistical significance was determined a priori with an alpha level of p < 0.05. Work-to-rest ratios were calculated during each set of the three matches, which provides data regarding energy system training specificity for coaches and trainers for developing exercise programing for beach volleyball athletes. Based on the time that the ball is in play, athletes competing in men's professional beach volleyball matches have a work-to-rest ratio of 1:5. They perform an average of 3.5 high-intensity movements per rally while the ball is in play. However, our data suggest no difference in the number of high-intensity movements per player or per team in determining winners versus losers.